Nonlinear causality between energy consumption and economic growth by timescale - Kim, Donggeun; Park, Young Joon (Energy Strategy Reviews, 2022)
Exploring the causal relationship between energy consumption and economic growth is important in energy economics. We performed an empirical re-examination of the causal interactions between these two factors in South Korea. As most previous studies in South Korea overlook the nonlinear behavior of energy consumption and economic growth, we examine the possible nonlinear relationship between them in the time-frequency domain. Moreover, we provide additional features of their nonlinear relationship with volatility spillovers on a timescale. The empirical findings have different implications for short-run GDP fluctuations, medium-run business cycles, and long-run economic growth. A unidirectional nonlinear causal relationship exists from economic growth to energy consumption in the short and medium run. However, in the long run, there is no nonlinear causal relationship between them.
Keywords: Causal relationships; Economic growths; Energy economics; Energy-consumption; Non-linear relationships; Nonlinear behaviours; Nonlinear causalities; South Korea; Time-scales; Wavelets decomposition; Economic growth; Energy consumption; Nonlinear causality; Wavelet decomposition